Specific initial (introductory) formulas in Albanian (decasyllabic) songs of the frontier warriors - Sivački Ana V. (Balcanica, 2013)
This paper primarily seeks to demonstrate the position and importance of specific initial (introductory) formulas in the Albanian songs of the frontier warriors (Alb. këngë kreshnikësh, këngë të kreshnikëve), proposing their classification into several categories. The analysis performed on the corpus consisting of 102 songs has resulted in a typology similar to the one in Detelić 1996. Such a classification serves as a starting point for further research and future mandatory study of structural and other concordances between the corresponding formulas in South Slavic epic, which could be useful in shedding light on the issue of originality of the Albanian songs.